Russian-German Cooperation: The Transdrift I Expedition to the Laptev Sea. - Kassens, Heidemarie; Karpiy, Valeriy Y (PANGAEA, 1994)
The TRANSDRIFT l expedition was part of the joint Russian-German ARCTIC '93 Expedition. During this campaign in the northern Laptev Sea the interdisciplinary research programs of the R/V Polarstern of the Alfred Wegener Institute for Polar and Marine Research, Germany and the Ivan Kireyev of the Arctic and Antarctic Research Institute of St. Petersburg, Russia, were closely coordinated. Dredges and cores taken have revealed numerous thin manganese crusts covering worm tubes, abundant thicker crusts on bivalve shells and stones, as well as some massive manganese nodules found in the eastern Laptev Sea.
Annotated record of the detailed examination of Mn deposits from the TRANSDRIFT I expedition in the Laptev Sea
Keywords: BCR; Box corer (Reineck); Comment; Date/Time of event; Deposit type; DEPTH, sediment/rock; Description; IK9306-5; IK9334-5; IK9338-5; IK9349-7; IK9358-5; IK9361-9; IK9365-8; IK9367-1; IK9370-6; IK9373A-6; IK9382-7; IK93Z5-4; Ivan Kireyev; Laptev Sea; NOAA and MMS Marine Minerals Geochemical Database; NOAA-MMS; Position; Quantity of deposit; Sample ID; Sediment type; Size; Substrate type; Transdrift-I